2014
DOI: 10.1159/000363039
|View full text |Cite
|
Sign up to set email alerts
|

Notch 3 Protein, not its Gene Polymorphism, is Associated with the Chemotherapy Response and Prognosis of Advanced NSCLC Patients

Abstract: Aim: To study the relation of NOTCH3 and its gene polymorphisms with the chemotherapy response and the prognosis of patients with Non-small cell lung cancer (NSCLC). Methods: A total of 594 patients with advanced stage of NSCLC (IIIA, IIIB and IV) NSCLC were enrolled. All patients received Platinum-based chemotherapy. The NOTCH3 expression in tumors and its gene polymorphisms were determined. In vitro, several NSCLC cell lines received the NOTCH3 over-expression vector and small interfering RNA (siRNA) to stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 28 publications
1
32
0
Order By: Relevance
“…However, chemoresistance poses a major obstacle to the successful use of drugs in the treatment of cancer [18]. Paclitaxel is an antimitotic agent that binds to microtubules, thereby stabilizing them against depolymerization and inhibiting cell replication by disrupting normal mitotic spindle formation [19].…”
Section: Introductionmentioning
confidence: 99%
“…However, chemoresistance poses a major obstacle to the successful use of drugs in the treatment of cancer [18]. Paclitaxel is an antimitotic agent that binds to microtubules, thereby stabilizing them against depolymerization and inhibiting cell replication by disrupting normal mitotic spindle formation [19].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that genetic Variants and protein expressions might affect the platinum-based chemotherapy response and prognosis of advanced NSCLC patients [36,37]. Platinum-based chemotherapy as a main treatment for lung cancer exerts its anti-cancer effect largely through the formation of bulky platinum-DNA adducts, which result in destabilization of the DNA double helix that otherwise blocks replication and inhibits transcription.…”
Section: Discussionmentioning
confidence: 99%
“…As a classical Notch signaling pathway, the CBF-1/RBP-Jk pathway plays a pivotal role in mammals [38]. Studies have shown that adjacent cells transfer Notch signals to each other via the binding of receptors and ligands through a signaling cascade to regulate cellular behavior, including, proliferation, development, organ formation and morphogenesis [38,39]. In general, the ligand such as JAGGED, which can be combined with membrane receptor NOTCH1 to conduct signals, eventually activates the expression of the primary target genes Hes1 and Hes5; the latter was shown to regulate cell proliferation and differentiation [40,41].…”
Section: Discussionmentioning
confidence: 99%